Mapping of Human Resources to Support the Development of Floral Village Tourism - Mujanah, Siti; Pristiana, Ulfi (Universitas Dr. Soetomo, 2021)
This research was conducted with the aim of formulating the mapping of Human Resources in order to support the development of floral village tourism, Banyuurip Village, Gresik District, East Java. This research was conducted using a descriptive method to obtain a Human Resources map consisting of identification of gender, age, educational background, work experience and competencies possessed by the people of Kampung Bunga in Banyuurip Village, Gresik. The data was taken through a survey with a questionnaire instrument to the community to support the growth of the tourist village in Banyuurip. After the data was collected, an analysis was carried out using descriptive analysis. The results showed that most of the respondents in this study were 60% men and 40% women, aged 30-50 years, on average had a secondary education and mostly working in the field of florists and flower farming. Furthermore, the average respondent has competency in the field of business and farming florists, and they were expert, because this job has been practiced for a long time and this requires special skills. They are very enthusiast when their village is developed into a tourist village and are willing to take an active role and take part in their respective fields. They also want some training in managing tourist villages, and other training such as planting and taking care of flowers, marketing training, compost making, culinary, catering and so on.